2007
DOI: 10.1155/2008/328172
|View full text |Cite
|
Sign up to set email alerts
|

The PPAR‐Platelet Connection: Modulators of Inflammation and Potential Cardiovascular Effects

Abstract: Historically, platelets were viewed as simple anucleate cells responsible for initiating thrombosis and maintaining hemostasis, but clearly they are also key mediators of inflammation and immune cell activation. An emerging body of evidence links platelet function and thrombosis to vascular inflammation. peroxisome proliferator-activated receptors (PPARs) play a major role in modulating inflammation and, interestingly, PPARs (PPARβ/δ and PPARγ) were recently identified in platelets. Additionally, PPAR agonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 218 publications
(245 reference statements)
0
18
0
1
Order By: Relevance
“…Activation of platelets consists of complex cellular responses: adhesion, aggregation, and secretion of compounds stored in platelet granules (Jane and Freedman 2005;Lundblad and White 2005). Platelet activation is a complex process, which is useful in hemostasis, but hyperactivity of platelets causes thrombosis, atherosclerosis, cardiovascular, and cerebrovascular disorders (stroke, heart attack), and is involved in inflammatory processes and cancers (Gawaz et al 2005;Spinelli et al 2008). Buczynski et al (1991) suggested that physical exercise affects platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of platelets consists of complex cellular responses: adhesion, aggregation, and secretion of compounds stored in platelet granules (Jane and Freedman 2005;Lundblad and White 2005). Platelet activation is a complex process, which is useful in hemostasis, but hyperactivity of platelets causes thrombosis, atherosclerosis, cardiovascular, and cerebrovascular disorders (stroke, heart attack), and is involved in inflammatory processes and cancers (Gawaz et al 2005;Spinelli et al 2008). Buczynski et al (1991) suggested that physical exercise affects platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rosiglitazone reduced thromboxane A 2 production and prevented the surface expression and release of sCD40L induced by thrombin (Akbiyik et al, 2004). Notably, most of these studies regarded rosiglitazone as only a PPARg agonist and tended to ascribe these platelet effects to PPARg stimulation without proper verification (Akbiyik et al, 2004;Ali et al, 2006;Bishop-Bailey, 2010;Moraes et al, 2010;Spinelli et al, 2008). Such interpretation was also attributed to the accompanying experimental evidence-the antiaggregatory activity of the PPARg agonist 15d-PGJ 2 (Akbiyik et al, 2004;Moraes et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic diabetic conditions cause platelet hyperreactivity, which contributes to the pathogenesis and progression of diabetic vascular complications. Hence, the vascular protective effects of thiazolidindiones may be attributed, at least to some extent, to their antiplatelet activity (Ray et al, 2006;Randriamboavonjy et al, 2008;Spinelli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Клинические данные свиде тельствуют о вовлечении PPAR и их лиганд в регуля цию воспалительных реакций в легких [12]. Впервые H.J.Patel et al [13] показали, что гладкомышечные клетки дыхательных путей (ГМКДП) человека экс прессируют PPARα и PPARγ, а активация PPARγ естественными (15d PGJ2) и синтетическими (си глитазон) лигандами подавляет индуцированный сывороткой рост ГМКДП более эффективно, чем дексаметазон, и индуцируют их апоптоз.…”
Section: роль Ppar и их лиганд при воспалительных процессах в легкихunclassified